PREVALENCE AND FACTORS ASSOCIATED WITH TYPE 2 DIABETES IN AVRANKOU, SOUTHERN BENIN - PADONOU, SETONDJI GERAUD ROMEO (My University, 2021)
ABSTRACT Objectives: In a context of epidemiological transition of chronic noncommunicable diseases in middle-income and low-income countries, the objectives of this study were to determine the community prevalence of type 2 diabetes and to research the associated factors. Methods: A descriptive and analytical cross-sectional study was conducted from July to September 2021 in Avrankou, a city located in the south-east of Benin. 402 subjects were recruited from whom the following data were collected: fasting capillary glycaemia, anthropometric measurements, sociodemographic and economic factors, nutritional information, practice of physical activity. A logistic regression model was made to identify the factors associated with diabetes defined by a glycaemia > 1.26 g/L. Results: Prevalence of diabetes in our sample was 13.18%. Mean age (SD) was 45.74 (7.89), the M/F sex ratio was 1.32. Most were civil servants or executives (40.81%), 44.53% had a BMI > 25, 40.05% were sedentary. Mean food consumption score was 32.79 and the food diversity score was 8.32. Age > 40 years (OR=2.34; p=0.000), BMI > 25 (OR=3.79; p=0.000), sedentary lifestyle (OR=2.09; p=0.001) and household wealth index (OR=1.94; p=0.02), were significantly associated with the occurrence of type 2 diabetes. Conclusion: This study highlights the need to intensify public health interventions to prevent the onset of diabetes in target populations, by acting on modifiable risk factors.
Keywords: Type 2 diabetes-Risk factors-BMI-Sedentary lifestyle -Household; wealth index